Tocilizumab (TCZ) Decreases Angiogenesis in Rheumatoid Arthritis Through Its Regulatory Effect on miR-146a-5p and EMMPRIN/CD147 - Zisman, Devy; Safieh, Mirna; Simanovich, Elina; Feld, Joy; Kinarty, Amalia; Zisman, Liron; Gazitt, Tal; Haddad, Amir; Elias, Muna; Rosner, Itzhak; Kaly, Lisa; Rahat, Michal A. (Frontiers in Immunology, 2021)
Background Angiogenesis is a major contributor to the development of inflammation during Rheumatoid arthritis (RA), as the vascularization of the pannus provides nutrients and oxygen for the infiltrating immune cells and proliferating synoviocytes. Tocilizumab (TCZ) is an anti-IL-6 receptor antibody that is used in the treatment of RA patients, and has been shown to exert anti-inflammatory effects. However, its effects on angiogenesis are not fully elucidated, and the molecular mechanisms regulating this effect are unknown. Methods We evaluated the concentrations of several pro- and anti-angiogenic factors and the expression levels of several microRNA molecules that are associated with RA and angiogenesis in serum samples obtained from 40 RA patients, before and 4 months after the initiation of TCZ treatment. Additionally, we used an in vitro co-culture system of fibroblasts (the HT1080 cell line) and monocytes (the U937 cell line) to explore the mechanisms of TCZ action. Results Serum samples from RA patients treated with TCZ exhibited reduced circulating levels of EMMPRIN/CD147, enhanced expression of circulating miR-146a-5p and miR-150-5p, and reduced the angiogenic potential as was manifested by the lower number of tube-like structures that were formed by EaHy926 endothelial cell line. In vitro, the accumulation in the supernatants of the pro-angiogenic factors EMMPRIN, VEGF and MMP-9 was increased by co-culturing the HT1080 fibroblasts and the U937 monocytes, while the accumulation of the anti-angiogenic factor thrombospondin-1 (Tsp-1) and the expression levels of miR-146a-5p were reduced. Transfection of HT1080 cells with the miR-146a-5p mimic, decreased the accumulation of EMMPRIN, VEGF and MMP-9. When we neutralized EMMPRIN with a blocking antibody, the supernatants derived from these co-cultures displayed reduced migration, proliferation and tube formation in the functional assays. Conclusions Our findings implicate miR-146a-5p in the regulation of EMMPRIN and propose that TCZ affects angiogenesis through its effects on EMMPRIN and miR-146a-5p.